Information vs. Entry Costs: What Explains U.S. Stock Market Evolution? - Peress, Joel (Journal of Financial and Quantitative Analysis, 2005)
Abstract I investigate whether changes in stock market participation costs can explain the long-term increase in the number of U.S. stockholders. I separate these costs into two components: an information cost (the cost of collecting market information), and an entry cost (all other costs, including commissions and fees), and disentangle their general equilibrium implications in a noisy rational expectations economy. While a falling information cost cannot explain the observed increase in stock market participation, a falling entry cost can account for this plus several other features of the U.S. economy, including the falling equity premium, rising return variances, and the boom in passive relative to active investing.